RELASI OTONOMI KHUSUS DAN PENGURANGAN KEMISKINAN DI PROVINSI ACEH - Ikhsan Ikhsan (Universitas Teuku Umar, 2015)
This study investigates the The relationship between special autonomi and impact of alleviation of poverty. Special autonomy in Aceh was designed to rebuild Aceh Post-Conflict and tsunami that had destroyed Aceh from the development and social political causing increased poor people. Special autonomy expected to be the solution of social problems and poverty in aceh province.To achieve a purpose of this research, used the theory decentralization asymmetrical that helps to see efforts pelaksaan decentralization at the provincial level in accordance with local knowledge to the problem of community social and confinement the level of poverty.This research uses the method the qualitative study by adopting descriptive aimed at to explain deeper on the impact of autonomy special on alleviation of poverty through technique observation, interviews and documentation. the results showed that the relationship between special autonomy and poverty has no significant effect Keyword : Special autonomy, poverty, policy, relationship